Design and Development of Low Cost Certified Green Building for Non Residential Existing Building (NREB) - Anuar , Mohamed Kassim; Jamri , Mohd Saifuzam; Othman, Md Nazri; Ab Rashid, Mohd Zamzuri (Trans Tech Publications, 2013)
The Green Building Index (GBI) is one of rating tool which are provides a prospect for building developers and owners for designing and constructing a green and sustainable buildings. The proposed low cost GBI buildings provide many advantages such as energy savings, water savings, a healthier indoor environment, and better connectivity to public transport. Besides, adoption of recycling and greenery for the projects and can reduce the impact on the environment. However, the implementation to certify as Green Building Index has a lot of concerns such as cost constraint, know how constraints and etc. Therefore, in this paper, the design and development of low cost certified green building by fulfilling the Green Building Index (GBI) is proposed in order to ease the development of green building to have better life for human and environment in this world in term of energy efficiency performances.